INTRODUCTION OF ENGLISH LESSON ON ELEMENTARY SCHOOL STUDENTS' IN PANEI DISTRICT, SIMALUNGUN REGENCY, NORTH SUMATERA - Aura Rahma Azzahra; Sholihatul Hamidah Daulay; Tazkiya Aulia Ibriza; Nazeeva Yusrina; Putri Anantasari Barus (Cahaya Ilmu Bangsa Institute, 2024)
In the 21st century, English proficiency is vital for educational and professional advancement. This study explores the introduction of English lessons in elementary schools in Panei District, Simalungun Regency, North Sumatra. The research highlights the importance of early English education for equipping students with essential skills to thrive in a globalized world. Despite the growing significance of English, rural areas like Panei District face challenges such as limited resources, insufficient trained personnel, and the need for culturally relevant teaching methods. The study utilizes a descriptive research approach combined with documentary analysis to examine the implementation and impact of English language programs. Findings indicate that early exposure to English enhances students' language awareness, engagement, and basic communication skills. However, challenges in resources and varying student proficiency levels were observed. Continuous support and teacher training are identified as crucial for the program’s sustained success. The study underscores the need for a structured approach and community involvement to effectively integrate English into rural educational settings.